Deixis Found in Kobe Bryant Interview Entitled “Love What You Do” - Rizki Arianto; Putu Nur Ayomi (Institut Pariwisata dan Bisnis Internasional, 2025)
This study is titled Deixis Found in Kobe Bryant Interview Entitled “Love What You Do”. The objectives of this study are to identify the deixis kinds employed in Kobe Bryant's interview as well as the predominate type. The data source was taken from YouTube, the researchers took the following actions in order to collect the data. Firstly, the researchers searched the video of Kobe Bryant Interview entitled Love What You Do in YouTube. Secondly, the researchers watched the video and read the script. Thirdly, note taking the utterances that contain of deixis. Fourth, based on the varieties of deixis, the researcher examined those types. This research employed a descriptive qualitative research design and used theory proposed by Yule (1996). The findings indicate there are three different types of deixis used in Kobe Bryant Interview involving person deixis, spatial deixis and temporal deixis. Personal deixis is the most dominant deixis found in Kobe Bryant interview because when Kobe Bryant recounted his struggles and experiences of becoming one of the best basketball players in the world, he used the words “I” and “you” a lot.